(untitled) (Dhaka University Journal of Science, 2022)
Bangladesh has a vast natural water resources. In order to determine the water quality parameters such as pH, EC, DO, BOD, TOC, ions i.e., NO3-, SO42-, PO43- and heavy metals, thirty surface water samples were collected from the southern part of Bangladesh including the coastal regions of Patuakhali district and Kuakata sea beach area during the dry season. The pH of water samples was ranged from 7.58 to 8.77 with an average of 8.15. The average conductivity value was 8.83±2 mS/cm. The average DO was 8.33±1.82 mg/L and BOD was 0.31±0.03 mg/L. TOC was found between 0.78 and 1.78 mg/L with an average of 1.24 mg/L. The concentration of NO3 -,SO42-, PO43- was determined by ion chromatography and only sulphate ion was detected in a very low concentration. Water samples from different sources were analysed for five metals by AAS and the concentrations of Pb, Cd, Mn, Hg and As were below 0.2, 0.01, 0.22, 0.001 and 0.005 mg/L, respectively. Dhaka Univ. J. Sci. 70(1): 49-57, 2022 (January)